The Educational Function of the Family in the Textbooks of the Horthy Era (Training and Practice : Journal of Educational Sciences, 2015)
This study is focusing on the family functions, especially the representation of the educational function of the family in the textbooks of the Horthy era. The adequate research method was content analysis of 16 textbooks, its analytical entities were words and pictures. In advance we can premise that deriving from the functions of the textbooks, the socializing functions are overrepresented in the documents, but the person attending to the educational function does not meet the preliminary expectations, that is the duties of men and women are not organized by traditional gender roles in particular cases.